The Forging of Dispersed Nano-Emulsion for Potential Feed Additive from Black Soldier Fly Essential Oil by Ultrasonication and Its Biological Efficacy - Sholeha, Novia Amalia; Sujarnoko, Tekad Urip Pambudi; Khotijah, Lilis; Astuti, Dewi Apri; Baihaqi, Muhamad; Komalasari, Kokom (Journal of Multidisciplinary Applied Natural Science, 2026)
Encapsulation technology was developed to address the issues of limited bioavailability and instability associated with black soldier fly oil (BSFO). This research synthesized a nano-emulsion of BSFO utilizing the ultrasonication method, while varying the sources of antioxidants (black seed oil (BSO) and curcumin) and emulsifiers (polyethylene glycol (PEG), whey protein isolate, and Tween 80). The FTIR analysis revealed that the nanoemulsion samples displayed peaks at 3500–3000 cm-1 (O–H stretching), 2900–2700 cm-1 (N–H stretching), and 1700–1500 cm-1 (C=O stretching), suggesting the presence of BSFO, curcumin, BSO, and the characteristics of the emulsifiers. Particle size analysis (PSA) indicated that the emulsion had an average particle size (Z-average) of approximately 229–686 nm. The nan’oemulsion containing PEG showed reduced particle sizes of 218 and 229 nm compared to those with other emulsifiers, attributable to the inherently smaller size of PEG. The HB (BSO with PEG emulsifier) showed a reduced particle size due to the smaller molecular size of the antioxidant BSO compared to curcumin. The polydispersity index (PI) values for HB and CB (curcumin with PEG emulsifier) were 0.3 and 0.2, respectively, indicating relatively homogeneous particles, consistent with the criterion of a PI value below 0.4. Biological assays showed that CB had the highest DPPH inhibition at 83%, while curcumin exhibited 90%, exceeding that of BSO. The inhibition zones of HB are 2.45 cm for Staphylococcus aureus and 2.70 cm for Escherichia coli, representing the highest levels of inhibition. In this study, PEG is the best emulsifier for achieving a smaller nanoemulsion particle size. PEG facilitates the incorporation of BSFO with antioxidants, enhancing stability, efficacy, and bioavailability in various applications, particularly in the medical and food sectors.